2009
DOI: 10.1177/0269215508098891
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory cluster randomized controlled trial of group exercise on mobility and depression in care home residents

Abstract: Group exercise can be delivered to care home residents with reduced mobility but it is not suitable for residents with severe cognitive impairment. An estimated sample size of 240 participants would be required to detect a clinically significant difference in the Rivermead Mobility Index with 90% power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
0
16
0
1
Order By: Relevance
“…The inclusion of such frail persons as nursing home residents in a study often lowers the compliance rate and makes it difficult to draw conclusions about intervention effects over time. In a study by Brittle et al [37], 82% completed all assessments, but only 43% attended all training sessions. In our study, 82.5% took part in the 3-month follow-up, and 68% of the IG completed the main part (≥10 weeks) of the intervention period despite the fact that the majority of the participants were cognitively impaired to some degree.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of such frail persons as nursing home residents in a study often lowers the compliance rate and makes it difficult to draw conclusions about intervention effects over time. In a study by Brittle et al [37], 82% completed all assessments, but only 43% attended all training sessions. In our study, 82.5% took part in the 3-month follow-up, and 68% of the IG completed the main part (≥10 weeks) of the intervention period despite the fact that the majority of the participants were cognitively impaired to some degree.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of training sessions (3-5 days/week) and the long period of intervention (12 weeks) also strengthened the study. Brittle et al [37] concluded that two exercise sessions per week for 5 weeks may not be enough to induce change in mobility in older residents. However, it can be questioned whether 3 months of intervention is a sufficient time period for optimal benefit, or if a longer period would have been needed for participants to reach their full potential.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, regular exercise therapy is not routinely available to care home residents (Brittle et al, 2009;O'Dea, Kerrison, & Pollock, 2000;Sackley, Gatt, & Walker, 2001). One recent study looking at the effect of group exercise on mobility and depression in care home residents, including those with cognitive impairment, concluded that 'group exercise is not suitable for residents with severe cognitive impairment', because they were 'unable to engage in exercise sessions' and 'struggled to follow instructions' and also some exhibited 'socially disruptive behaviour' (Brittle et al, 2009).…”
Section: Current Use Of Exercise In Residential Homesmentioning
confidence: 99%
“…Teri et al (2008) found 'teaching both cognitively impaired participants and their caregivers, behavioural and problem solving strategies for establishing and maintaining' any programme; and 'providing handouts, information' to be helpful in sustaining the exercise programme. In focusing on ways to 'maximize enjoyment' of exercise and in using a collaborative approach, it has been suggested that 'better adherence may be achieved by educating staff, residents and relatives about the benefits of exercise and negotiating times' (Brittle et al, 2009). …”
Section: Benefits Of Exercisementioning
confidence: 99%
See 1 more Smart Citation